Diverse functions of the inward-rectifying potassium channel Kir5.1 and its relationship with human diseases - Zhang, Chaojie; Guo, Jia (Frontiers in Physiology, 2023)
The inward-rectifying potassium channel subunit Kir5.1, encoded by Kcnj16, can form functional heteromeric channels (Kir4.1/5.1 and Kir4.2/5.1) with Kir4.1 (encoded by Kcnj10) or Kir4.2 (encoded by Kcnj15). It is expressed in the kidneys, pancreas, thyroid, brain, and other organs. Although Kir5.1 cannot form functional homomeric channels in most cases, an increasing number of studies in recent years have found that the functions of this subunit should not be underestimated. Kir5.1 can confer intracellular pH sensitivity to Kir4.1/5.1 channels, which can act as extracellular potassium sensors in the renal distal convoluted tubule segment. This segment plays an important role in maintaining potassium and acid-base balances. This review summarizes the various pathophysiological processes involved in Kir5.1 and the expression changes of Kir5.1 as a differentially expressed gene in various cancers, as well as describing several other disease phenotypes caused by Kir5.1 dysfunction.